The Marxist Ecocriticism Of Capitalism In Paolo Bacigalupi’s The Water Knife - Aisyah, Restu; Supsiadji, Mateus Rudi (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2025)
This study analyzes capitalism in Paolo Bacigalupi's The Water Knife using a Marxist ecocritical approach. The research focuses on the commodification of water resources as a form of capitalist exploitation and its social impacts. This study employs Marxist ecocritical theory, which combines critiques of capitalism with environmental issues. This study uses an extrinsic literary approach that combines sociology of literature and ecocriticism to analyze the narrative and dialogue in the novel. Data was collected through reading and note-taking techniques, then analyzed using descriptive analysis techniques. The study finds that water is commodified through privatization, water rights, infrastructure control, and premium access, making it available only to those who can afford it. This creates inequality and unfair distribution. The novel shows social impacts such as economic gaps between rich and poor, environmental damage from overexploitation, alienation and individualism among characters, housing crises, poverty, and declining social welfare. This research contributes to literary studies by offering a new perspective on how water is exploited under capitalism and how this affects society. Keywords: capitalism, environmental crisis, water commodification